2021
DOI: 10.1017/jsi.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

‘Not Enough Time’: Identifying Victorian Teachers’ Perceptions of the Facilitators and Barriers to Supporting Improved Student Behaviour

Abstract: Students exhibiting behaviours of concern are at increased risk of poor outcomes during their school years. The implementation of school-wide positive behavioural interventions and supports (SWPBIS) has repeatedly been shown to be an effective, evidence-based approach that supports teachers to select and adopt effective practices to meet the social and behavioural needs of all learners. Implementation of SWPBIS within Australian schools is increasing. Although there is considerable evidence supporting the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In doing this, responsive tiered training models may allow for efficient allocation of the costliest resources (e.g., coaching) while minimizing the time commitment for busy teachers (R. A. Fox et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing this, responsive tiered training models may allow for efficient allocation of the costliest resources (e.g., coaching) while minimizing the time commitment for busy teachers (R. A. Fox et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that teacher motivation might vary based on personal factors (such as the perceived value of IPD or alignment with teachers' personal choices and interests; Zhang et al, 2021), school-level factors (such as workload, time, and support from colleagues; R. A. Fox et al, 2021), and systems-level factors (such as whether IPD is mandatory or optional, or whether IPD occurs during or outside of working hours; McMillan et al, 2016).…”
Section: Challenges With In-service Teacher Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, this aligns with the tiered logic of MTSS frameworks for students and ensures that supports are provided to match the level of individual need (McIntosh & Goodman, 2016). In doing this, responsive tiered training models may allow for efficient allocation of the costliest resources (e.g., coaching), while minimizing the impact on time poor teachers (Fox et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They have insufficient time to adequately prepare for lessons and, while wanting support, do not have time for lengthy professional learning activities (Lovison & Mo, 2022). Teachers have reported that lack of resources, time and training are significant barriers to their ability to implement evidence-based behavior support practices (Fox et al, 2021). Without high-quality training, teachers do not have the opportunity to develop sufficient skills to fluently implement effective, evidence-based practices in their own contexts (Mitchell et al, 2017).…”
Section: Barriers To High-quality Professional Developmentmentioning
confidence: 99%